Lung function of tuberculosis patients after completion of treatment in Sidama, South Ethiopia - Woldesemayat, Endrias Markos; Vera, Jaime H.; Tanner, Clea; Tamiso, Alemu; Assefa, Amare; Woldesenbet, Yohannes Markos (Frontiers in Medicine, 2025)
IntroductionLung function impairment are commonly reported after treatment of pulmonary tuberculosis (TB). This study aimed to examine lung function parameters among adults who have undergone treatment for pulmonary TB.MethodsA comparative cross-sectional study was conducted in eight rural communities of Dale district of Sidama Region, Southern Ethiopia. The post-TB group were smear-positive TB patients who successfully completed TB treatment between 2010 and 2021, while controls were selected from the neighbors of these participants with no documented history of TB. Lung function tests were conducted using a portable spirometer, and pulmonary symptoms were assessed using the Saint Georges Respiratory Questionnaire. Obstructive pulmonary impairment was defined as the ratio of FEV1/FVC below 70% and restrictive impairment was defined as having a normal FEV1/FVC ratio with a low FEV1. Data were entered and analyzed using SPSS version 25 statistical package.ResultsWe enrolled 167 TB cases and 156 controls in the study. The median (IQR) was 38 (21) years for cases and 35 (21.75) years for controls. The median (IQR) time after completion of TB treatment was 24 (31.75) months for the TB cases. A higher proportion of post-TB participants (101/167 (60.5%; 95% confidence interval (CI), 52.9–67.6%)) than controls (63/156 (40.4%; 95% CI, 33.0–48.2%)) had obstructive impairment, p = 0.01. Thirty eight (22.8; 95% CI, 17.1–29.7) post-TB participants and 39 (25.0%; 95% CI, 18.9–32.3%) controls had restrictive impairment; p = 0.3. Post-TB participants had high risk of obstructive pulmonary impairment (adjusted hazards ratio [aOR], 2.1; 95% CI, 1.3–3.3) and chronic obstructive pulmonary diseases symptoms scores (aOR, 73.0; 95% CI, 35.3–151.2). BMI was associated with obstructive impairment, (aOR, 1.6; 95% CI, 1.0–2.6) and the post-TB participants had increased risk of any impairment (aOR, 2.2; 95% CI, 1.1–4.5).ConclusionPost-TB participants had greater risk of pulmonary impairment and respiratory symptoms. Post-TB treatment follow-up care is suggested to quickly identify and manage pulmonary impairment.